Plateau regression in estimating the optimal plot size in papaya experiments in a greenhouse (Research, Society and Development, 2020)
The papaya culture has great socioeconomic importance in Brazil, although research with this fruit is little explored. Knowledge of the optimal plot size contributes to conducting experiments with greater precision and, consequently, increases the cost/benefit ratio of the culture. Thus, this research aim at estimating the optimal plot size for experiments in a greenhouse, with hybrid papaya, using the segmented regression model with linear plateau, based on a uniformity test with 100 basic units (ub). Several sizes and shapes of plots were simulated, in which each fruit was considered first as a basic unit (plot) up to 50 plants per basic unit. To estimate the optimal plot size, the segmented regression model with a linear plateau was used. After all, the recommended optimal plot size consisted of 12 plants.